Developing enterprise collaboration: a methodology to implement and improve interoperability. Issue 5 (12th June 2016) - Daclin, Nicolas; Chen, David; Vallespir, Bruno
Abstract : The aim of this article is to present a methodology for guiding enterprises to implement and improve interoperability. This methodology is based on three components: a framework of interoperability which structures specific solutions of interoperability and is composed of abstraction levels, views and approaches dimensions; a method to measure interoperability including interoperability before (maturity) and during (operational performances) a partnership; and a structured approach defining the steps of the methodology, from the expression of an enterprise's needs to implementation of solutions. The relationship which consistently relates these components forms the methodology and enables developing interoperability in a step-by-step manner. Each component of the methodology and the way it operates is presented. The overall approach is illustrated in a case study example on the basis of a process between a given company and its dealers. Conclusions and future perspectives are given at the end of the article.